FORMULASI DAN UJI DAYA HAMBAT SABUN CAIR EKSTRAK ETANOL SERAI WANGI (Cymbopogon nardus L) TERHADAP PERTUMBUHAN Staplylococcus aureus - Rinaldi, Rinaldi; Fauziah, Fauziah; Mastura, Rizka (Jurnal Riset Kefarmasian Indonesia, 2021)
Citronella (Cymbopogon Nardus.L) contains essential oil compounds, saponins, polyphenols and flavonoids which are antibacterial. The use of active compounds of Citronella is formulated into antibacterial liquid soap preparations. This study aims to determine the characteristics of liquid soap and its inhibition against the growth of Staphylococcus aureus. This research is experimental to formulate liquid soap containing ethanol extract of lemongrass sticks at concentrations of 9% (F1), 18% (F2) and 24% (F3). The test parameters for liquid soap preparations include organoleptic test (shape, aroma, color), homogeneity test, pH test, foam height test, foam stability test, free alkaline test and inhibition test against the growth of Staphylococcus aureus using the Kirby-Bauer method. The results showed that the liquid soap preparations in the F1, F2 and F3 formulas were liquid, had a distinctive aroma of Citronella and were brown in color, homogeneous. The pH values, foam height, foam stability and free alkaline content of liquid soap were F1 (12; 70 mm; 85.7% and 0.14%), F2 (11. 80 mm, 87.5% and respectively). 0.10%), F3 (10.100 mm, 90% and 0.08%). The formula inhibition zone diameters are 32.06 mm, 25.6 mm and 29.2 mm, respectively. The conclution is the characteristics of the liquid soap with the ethanol extract of Citronella (Cymbopogon Nardus.L) meet the requirements as liquid soap. The greatest inhibitory effectiveness on the growth of Staphylococcus aureus was a formula at a concentration of 24% (F3) with a strong category.